The United Nations convention on contracts for the international sale of goods (cisg) and the Common Law: the challenge of interpreting Article 7 (2015)
The interpretative methodology applied in Common Law CISG jurisprudence has driven a disparity of reasoning that hinders a uniform application of its provisions. This result is inconsistent with CISG Article 7 which mandates interpretation of the convention in accordance with its international character and the need to promote uniformity. This paper discusses the multiple aspects that have affected the uniform interpretation of CISG norms, including a reference to the case law in USA, Australia and Italy. Finally, the Unidroit principles are presented as an aid to overcome the difficulties in the application of CISG article 7.